RANCANG BANGUN APLIKASI STOCK OPNAME PADA PT. ARIE MUTI BERBASIS ANDROID - Irmawati Carolina; Kresna Ramanda; Arief Rusman; Ikhwan Akbar (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Stocktaking is a calculation and adjustment of the stock of goods and assets owned by a store or company in a warehouse or storefront with stock data contained in the company's database system. During stock taking, the entry and exit activities of goods cannot be carried out. This causes the company to be irregular in conducting stock taking. The purpose of this research is to create a system and application that can simplify the process of managing stock operations. The research method used in this research is using extreme programming method. With this method and the android application, it is expected that the stock management data management process will be more flexible because there is no need to use a computer but only with an Android-based smartphone. With this application, you only need to use the camera on the smartphone to scan the item in question without the need to type on the computer